2011
DOI: 10.1158/0008-5472.can-10-2743
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular CD24 Inhibits Cell Invasion by Posttranscriptional Regulation of BART through Interaction with G3BP

Abstract: We report a novel function for the CD24 molecule in pancreatic cancer cells. Intracellular CD24 is associated with stress granules that contain specific mRNAs and RNA-binding proteins that regulate mRNA stability and translation. Intracellular CD24 in stress granules is associated with G3BP, a phosphorylation-dependent endoribonuclease. The vesicles in which the CD24/G3BP complex localizes are transported toward cell protrusions in migrating cells. We show that G3BP binds to and degrades Binder of Arl Two (BAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 31 publications
(34 reference statements)
5
78
2
Order By: Relevance
“…A recent study of pancreatic ductal adenocarcinomas showed that CD24 expression was exclusively up-regulated in well-differentiated tumors, whereas CD24 expression was absent in undifferentiated tumors (33). Our study supports the previous study's proposal that cytoplasmic CD24 expression inhibits tumor cell migration thus inhibiting undifferentiated features (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…A recent study of pancreatic ductal adenocarcinomas showed that CD24 expression was exclusively up-regulated in well-differentiated tumors, whereas CD24 expression was absent in undifferentiated tumors (33). Our study supports the previous study's proposal that cytoplasmic CD24 expression inhibits tumor cell migration thus inhibiting undifferentiated features (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…1D). We confirmed that knockdown of BART in S2-013 and PANC-1 enhanced cell motility into a wounded area of confluent cultures compared to control cells (10). BART and ARL2 were both recruited to the leading edges during wound healing of control S2-013 cells (upper panels in Fig.…”
Section: Colocalization Of Bart and Arl2 In Pdac Cellssupporting
confidence: 73%
“…2C). We previously reported that suppression of BART enhanced cell invasiveness in Matrigel invasion assays (10). Pretreatment of control S2-013 cells with C3 induced the same level of invasive activity in the Matrigel assay as that induced by knocking down BART (Fig.…”
Section: Colocalization Of Bart and Arl2 In Pdac Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…We previously reported that binder of Arl two (BART) inhibits retroperitoneal invasion and liver metastasis of pancreatic ductal adenocarcinoma (PDAC) cells in an orthotopic xenograft model (12). Our findings provide an explanation for the oncogenic function of G3BP to induce tumor invasion and metastasis by mediating BART mRNA decay.…”
Section: Introductionmentioning
confidence: 53%